(2√х + √у)*(3√х - 2√у) (1-√а)*(1+√а+а)
2)Перевести в подобные слагаемые
5√5 - 3√5 - √5
√7 - 4√7 + √7
6√а + √а +4√n - 7√n
плс

КлименковЛеонид КлименковЛеонид    1   14.12.2021 15:27    0

Ответы
Fantik14rus Fantik14rus  04.02.2022 05:34

( 2 \sqrt{ x } + \sqrt{ y} ) ( 3 \sqrt{ x } -2 \sqrt{ y})\\=2 \sqrt{ x }* 3 \sqrt{ x }-2 \sqrt{ x }*2 \sqrt{ y}+ \sqrt{ y} *3 \sqrt{ x }-\sqrt{ y} *2 \sqrt{ y}=\\6x-4\sqrt{ x }\sqrt{ y}+3\sqrt{ x }\sqrt{ y}-2y=6x-\sqrt{ xy }-2y\\ 5 \sqrt{ 5} -3 \sqrt{ 5} - \sqrt{ 5}= 2 \sqrt{ 5}- \sqrt{ 5}= \sqrt{ 5}\\ \sqrt{7} -4\sqrt{7 } + \sqrt{ 7 } = -3\sqrt{7 }+ \sqrt{ 7 }= -2\sqrt{7 }\\ 6 \sqrt{ a} + \sqrt{ a } +4 \sqrt{ n} -7 \sqrt{ n}=7 \sqrt{ a}-3 \sqrt{ n

Объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра